CORPORATE SOCIAL RESPONSIBILITY (CSR) REPORTING CHALLENGE: AN OVERVIEW - Jeriji, Maher (The journal of contemporary issues in business and government, 2022)
Corporate social responsibility (CSR) reporting should reduce information asymmetry and provide an accurate picture of overall company performance. However, managers do not hesitate to adopt less transparent communication strategies, especially when the legitimacy of their companies is threatened. This raises the question of the usefulness of CSR reporting from the perspective of the various stakeholders. This is especially challenging as managers can choose between reporting quantitative and narrative CSR information, as well as information that may have a positive impact on society and other harmful (negative) information.